Perlindungan Hukum Pemegang Polis Asuransi Syariah Berdasarkan Undang-Undang Nomor 40 Tahun 2014 Tentang Perasuransian - Prayogo, Iip Harnoto; Syufaat, Syufaat (Alhamra Jurnal Studi Islam, 2023)
This research was conducted to find out the legal protection that Sharia insurance policyholders can have based on law number 40 of 2014 concerning insurance, in the event of a dispute between Sharia insurance policyholders and an insurance company through an insurance agreement. This study uses a juridical method that is guided by the norms of the rule of law contained in statutory regulations. Sources of data used include secondary data, primary data, and tertiary data. Primary legal materials are legal and statutory provisions that will be examined, including 1) Law Number 40 of 2014 concerning Insurance Business; 2) Fatwa of the national sharia council No. 21/DSNMUI/X/2001 concerning general guidelines for Sharia insurance; and 3) Supreme Court Regulation No. 2 of 2008 concerning Sharia Economic Compilation Law. Secondary legal material is in the form of written source literature on the main questions of this study in the form of legal treatises, books, and legal journals. While tertiary legal materials for this research include legal dictionaries, legal research books, journals, and internet research. The results of this study are protection for policyholders or insureds based on dispute resolution and Sharia insurance legal entities according to law number 40 of 2014. The insurer as a party bound by an insurance contract with an insurance company is protected by Article 53 which regulates insurance guarantee schemes, and Article 54 which regulates the settlement of insurance disputes through mediation. In the principle of Islamic insurance, namely, ta’Äwun ’ala al birr wa al taqwa (beneficial kindness) and al ta’mÄ«n (sense of security).